PEMANFAATAN ALGORITMA APRIORI UNTUK PENINGKATAN EFISIENSI PRODUKSI AKUAKULTUR DI SUMATERA UTARA - Fricles A Sianturi (Jurnal Ilmu Komputer Ruru, 2024)
Aquaculture is a crucial sector for supporting food security and the economy in North Sumatra Province. However, aquaculture production in this region faces several challenges, such as low production efficiency and suboptimal resource utilization. This study aims to optimize aquaculture production by applying the Apriori Algorithm and Association Rule Method. A case study was conducted at the North Sumatra Provincial Department of Marine Affairs and Fisheries. Aquaculture production data, including fish species, feed, environmental conditions, and farming techniques, were collected and analyzed using the Apriori Algorithm. This algorithm was used to identify significant patterns and relationships among these factors that could enhance production. The results of the study show that the application of the Apriori Algorithm successfully identified the most effective factor combinations for improving aquaculture production. For instance, it was found that a certain combination of feed types with specific environmental conditions resulted in a significant increase in production. These findings provide valuable insights for strategic decision-making in the management and development of the aquaculture sector in North Sumatra. Thus, this research contributes to the sustainability and productivity improvement of aquaculture in the region, and offers a scientific basis for more effective planning and policy implementation in the aquaculture sector